The Correlation of Health Literacy Related to Health-Promoting University towards Healthy Behavior Among The Academic Community - Windri Lesmana Rubai; Siti Masfiah; Arrum Firda Ayu Maqfiroch (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2023)
Background: Health is a substantial factor in creating distinguished human resources. University, as a prominent institution in society, has a role in creating distinguished human resources that could be realized with the campus policy concerned with health issues. Universitas Jenderal Soedirman (UNSOED) has not made a specific health Promoting University (HPU) policy or a healthy campus program. The importance of health problem surveillance in the case of the academic community –and its determinant–and its result could be fundamental, either in the decision-making or policy planning related to the creation of a healthy campus at UNSOED. The study intends to analyze the correlation between health literacy and the attitude of HPU towards healthy behavior among the academic community at UNSOED.Method: The study uses a quantitative method with a cross-sectional. The data acquisition was carried out by online sampling from August until September 2021. A total of 238 respondents were involved: lecturers, academic staff, and students from 12 faculties at UNSOED. The data respondents were analyzed with chi-square. Results: The majority of respondents were not infected with a chronic disease, were immune from COVID-19 and had no allergies either. Most of the respondents have moderate health literacy, supporting the policy about HPU, but most still lack consciousness to apply healthy behavior on campus. The correlation between health literacy and healthy behavior in the impacted group could only be found in the UNSOED lecturer (p-value 0.034), instead of the other groups. There is no impacted relation between the attitude and the healthy behavior of all respondent group. It is necessary to develop a health promotion university program that follows the academic community's needs.